2020
DOI: 10.3390/met10101354
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Capillary Force of Binder-Jetting Printing Ti6Al4V and Mechanical Properties under High Temperature Sintering by Mixing Fine Powder

Abstract: Binder jet 3D printing (BJ3DP) is an additive manufacturing technology that selectively deposits binder on powder to form a three-dimensional green body followed by sintering process. The low strength of green body and metallurgical issues limit the manufacture of Ti6Al4V parts with high-performance and that are lightweight. In this study, thermal-bubble inkjet technology was used to print Ti6Al4V parts via jetting low-concentration in-situ polymer binders. In addition, a method for mixing fine powder was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Tang et al experimentally verified the different wettability of the binder on two different particle size distributions. The particle size determining a higher powder bed density produces a slight increase in the contact angle and a dramatic increase in infiltration time [34]. Therefore, powders in a dense arrangement (high powder bed density) determine a high saturation level, while low packed powders (low powder bed density), are related to a lower saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…Tang et al experimentally verified the different wettability of the binder on two different particle size distributions. The particle size determining a higher powder bed density produces a slight increase in the contact angle and a dramatic increase in infiltration time [34]. Therefore, powders in a dense arrangement (high powder bed density) determine a high saturation level, while low packed powders (low powder bed density), are related to a lower saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…An eco-friendly chelator-based binding mechanism for BJM3DP was proposed and the feasibility of achieving an effective 3D printing system was demonstrated in this study. In the field of BJM3DPs, a few candidates for green-solvent-soluble binders have been reported so far, such as polyvinyl alcohol (PVA) 37 , 42 , 57 , polyacryl amide (PAM) 58 , polyvinyl pyrrolidone (PVP) 59 , and maltodextrin 37 , some of which were adopted from successful demonstrations in the field of ceramic BJ3DPs for biomedical applications 58 . However, the mechanical properties of the printed metal objects based on them, even with highly tough Ti−6Al−4V alloy, were mostly rather less competitive for broad applications compared to the ones based on common binder materials developed without considerations for eco-friendliness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on improving this process, applied to different materials. Tang et al [7] optimized the binder jetting process for inkjet printing Ti6Al4V parts with excellent properties. Mariani et al [8] demonstrated the feasibility of binder jetting technology to print WC-Co parts.…”
Section: Of 16mentioning
confidence: 99%